TINJAUAN MASLAHAH MURSALAH DALAM PEMBENTUKAN KELUARGA SAKINAH MELALUI DIKLAT MU’ASYAROH SANTRI TINGKAT TAKHASUS PONDOK PESANTREN DARUL HUDA MAYAK PONOROGO - Munfaridah, Imroatul; Abdurrohman, Muchammad (Al-Usroh, 2024)
Mu'asyaroh training is an activity carried out by special level students at the Darul Huda Mayak Tonatan Ponorogo Islamic boarding school, which is an annual mandatory activity, this is based on the importance of a student's understanding of pre-marital material. Because there are many factors in divorce caused by a lack of understanding between husband and wife in carrying out muasyaroh in marriage. Therefore, it is very important to carry out muasyaroh training activities to prevent divorce. The aim of this research is to determine the function and purpose of Mu'asyaroh Santri Training at the Special Level at the Darul Huda Mayak Islamic Boarding School, Ponorogo and to find out the benefits of Mu’asyaroh Santri Training at the Special Level at the Darul Huda Mayak Islamic Boarding School, Ponorogo in Forming a Sakinah Family. The research method used uses qualitative research methods. The data analysis uses interview techniques, observation, data collection and so on. So it can be concluded that muasyaroh training activities have a goal to shape the Islamic thinking patterns of students so that they become more mature in navigating the family ship, providing insight into what students need to prepare for when they are married. As a provision in avoiding the occurrence of divorce, forming harmony in the household with the aim of achieving a sakinah family. The aim and benefit of Mu’asyaroh training activities is that students can understand the importance of preparation before carrying out a wedding. Can form harmony in the household to create a sakinah mawadah warohmah family. And if the muasyaroh training activities are linked to the concept of maslahah murlahah, it can be concluded that the Mu’asyaroh training activities at the Darul Huda Mayak Ponorogo Islamic boarding school have a maslahah side for takhasus students. Apart from that, Mu’asyaroh training activities at the Darul Huda Mayak Ponorogo Islamic boarding school also fulfill the requirements of Maslahah Murlah. Mu’asyaroh training activities that can be categorized as maslahah hajiyah are maslahah that support Mas}lahah daruriyah in basic human needs.